Analisis Kemampuan Keuangan Daerah dalam Mendukung Pembangunan Kota Palangka Raya - Pratiwi Subianto; Irawan, Irawan (FKIP, Universitas Palangka Raya, 2022)
This study uses statistical analysis and trends to see the development of the Degree of Fiscal Decentralization, Ratio of Regional Original Income to Total Regional Revenue, Degree of Fiscal Autonomy and Regional Fiscal Capacity of Palangka Raya City during the period 2008-2017 showing positive developments. Meanwhile, for the degree of Fiscal Decentralization, the Ratio between Tax and Non-Tax Revenue Sharing, the Contribution of Regional Assistance to Total Regional Revenue and Fiscal Needs for the City of Palangka Raya for the period 2008-2017 showed negative results. This situation shows that the regional financial capacity of Palangka Raya City in supporting development independently tends to be lacking.